DAILY VARIATION IN EARTH'S MAGNETIC FIELD - Tihomir Gregl (Rudarsko-geološko-naftni Zbornik, 2000)
Daily variation in Earth's magnetic field is changed during the time of the day and according to Earth's latitude and lengthwise. Due to great sensitivity of new proton magnetometers there is a question how daily variation vary according to distance from the base. To solve this problem, simultaneously was surveyed daily variation on the base and on the points which were on different distances from the base point (the paper is published in Croatian).